Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1038/sj.bjc.6600763
|View full text |Cite
|
Sign up to set email alerts
|

Association between telomere length and VH gene mutation status in chronic lymphocytic leukaemia: clinical and biological implications

Abstract: The immunoglobulin V H gene mutation status can divide B-cell chronic lymphocytic leukaemia (CLL) into two entities with a different clinical course. Cases with unmutated V H genes, considered to evolve from pregerminal centre (GC) cells, have a worse outcome compared to cases showing mutated V H genes, that is, post-GC derived. Also, telomere length has been reported to be of prognostic significance in CLL. Interestingly, telomerase becomes activated during the GC reaction and an elongation of the telomeres o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
31
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 36 publications
10
31
0
3
Order By: Relevance
“…1 CD38 positivity (P < 0.0001), and 11q/17p deletion (Fig. 1B), as documented earlier by us and others [9][10][11][12][13][14]. For the first time, we observed that mutations in the NOTCH1 and SF3B1 genes were associated with particularly short TL, similar to patients with 11q or 17p deletion (Fig.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…1 CD38 positivity (P < 0.0001), and 11q/17p deletion (Fig. 1B), as documented earlier by us and others [9][10][11][12][13][14]. For the first time, we observed that mutations in the NOTCH1 and SF3B1 genes were associated with particularly short TL, similar to patients with 11q or 17p deletion (Fig.…”
Section: Introductionsupporting
confidence: 71%
“…The future status of these biomarkers as a basis for clinical decision makings has not yet been fully defined, although the immunoglobulin heavy chain variable (IGHV) gene mutational status and in particular the presence of certain recurrent genomic aberrations (i.e., 11q2, 112, 13q2, 17p2) are commonly applied biomarkers [5][6][7]. Several studies have lately indicated TL as a potential prognostic marker in CLL, whereby short telomeres may predict poor clinical outcome [8][9][10][11][12][13][14][15]. Furthermore, a strong association has been reported between short TL and IGHV-unmutated CLL [11], and high-risk genomic aberrations such as del(17p) [13].…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Previous studies have shown that TL associates with IGHV homology, high-risk cytogenetics and poor TFS. 25,26 Subsequent reports outlined the existence of patients in which discordance exists between TL and IGHV-MS and suggested a superior predictive value of TL. 28,29 Finally, Roos et al 47 were able to link TL with poor cytogenetics in a series of 152 patients, including samples collected both at diagnosis and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have shown that short telomeres and expression of h-tert, the catalytic subunit of telomerase, are poor prognostic factors in this neoplasm. [24][25][26][27] Although early studies postulated that telomere length (TL) was mostly acting as a surrogate marker for IGHV-MS, a number of subsequent reports indicated that in discordant cases TL performed better than IGHV-MS, suggesting that TL deserved further consideration as a prognostic biomarker in CLL. 28,29 Despite these encouraging results, additional experience needs to be accumulated on TL as a prognostic marker in CLL.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of SHM in the cell may reflect the number of rounds of divisions the cells have undergone in the GC which is supported by a correlation with telomere length and degree of mutations (97). Therefore, it is possible that mutated cells which have divided more frequently during the GC reaction (highly mutated, >5%) may be more anergic/resting post GC when they transform to CLL and therefore represent more benign tumor cells.…”
Section: Somatic Hypermutation In Cllmentioning
confidence: 94%